The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1997
DOI: 10.1038/sj.bmt.1700633
|View full text |Cite
|
Sign up to set email alerts
|

A phase I trial of recombinant human interleukin-1β(OCT-43) following high-dose chemotherapy and autologous bone marrow transplantation

Abstract: Summary:The use of lineage-specific hematopoietic growth factors such as GM-CSF and G-CSF shortens the duration of neuWe studied the effects of escalating doses of recombitropenia following high-dose chemotherapy and ABMT. 1-3 nant human IL-1␤ in patients receiving high-doseRecently with molecular cloning much interest has emerged chemotherapy and ABMT for metastatic breast cancer in the use of growth factors, which have multilineage proor malignant melanoma. Sixteen patients received ILliferative effects, to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
8
0
2

Year Published

1999
1999
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 4 publications
0
8
0
2
Order By: Relevance
“…G 1 CDK activity and G 1 cyclin availability define a final common pathway for growth factors (3) and cytostatic cytokines (4). IL-1␤ is a prototypical proinflammatory cytokine that exerts a plethora of biological activities, including tumor regression (5). The tumor-suppressing property of IL-1␤ has been attributed mostly to its ability to prime antitumor immunity (6), but the mechanism for its direct cytostatic actions in suppressing cell cycle progression is largely unknown.…”
Section: Il-1␤ Suppresses Prolonged Akt Activation and Expression Of mentioning
confidence: 99%
“…G 1 CDK activity and G 1 cyclin availability define a final common pathway for growth factors (3) and cytostatic cytokines (4). IL-1␤ is a prototypical proinflammatory cytokine that exerts a plethora of biological activities, including tumor regression (5). The tumor-suppressing property of IL-1␤ has been attributed mostly to its ability to prime antitumor immunity (6), but the mechanism for its direct cytostatic actions in suppressing cell cycle progression is largely unknown.…”
Section: Il-1␤ Suppresses Prolonged Akt Activation and Expression Of mentioning
confidence: 99%
“…IL-6 injection produces hyperalgesia, and in IL-6 Ϫ/Ϫ mutants, heat sensitivity of nociceptors has been shown to be reduced (Zhong et al, 1999). Second, some cytokines such as TNF-␣ or IL-1␤ have been used for adjuvant chemotherapy, but approximately one-half of the treated patients developed pain syndromes and complained about local tenderness at the injection site (Kemeny et al, 1990;Del Mastro et al, 1995;Elkordy et al, 1997). In experimental models, TNF-␣ and IL-1␤ induced excitation in nociceptors and hyperalgesia (Ferreira et al, 1988;Cunha et al, 1992;Sorkin et al, 1997;Kanaan et al, 1998;Sommer et al, 1998Sommer et al, , 1999, and both are suggested to activate receptor-associated kinases, e.g., IL-1 receptor-associated kinase (IRAK) (Cao et al, 1996).…”
mentioning
confidence: 99%
“…beim Malignen Melanom (Protokoll: 4-32 ng IL-1β/kg/Tag, Beginn 3 h nach ABMT für 7 Tage) [13]. die ᭤ Expansion von Knochenmarkzellen ex vivo im Rahmen einer Chemotherapie oder s.c. Applikation nach Hochdosischemotherapie und autologer Knochenmarktransplantation z.B.…”
Section: Therapiemöglichkeiten Der Einsatz Von Il-1unclassified